2018
DOI: 10.1002/adfm.201805570
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Area, Semitransparent, and Flexible All‐Polymer Photodetectors

Abstract: Photodetectors, converting optical signals from specific wavelengths to electrical signals, have many applications on photoimaging, optical communication, and environmental monitoring. Solution-processed organic photodetectors (OPDs) based on organic materials emerge promise especially for wearable electronics and smart buildings. In this work, new all-polymer photodetectors (all-PPDs) are developed based on bulk-heterojunction active layers which incorporate a donor polymer and an acceptor polymer. The invert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 38 publications
1
72
0
Order By: Relevance
“…But in practical condition, due to the disordered nature and unavoidable surface doping, the carrier density is always much higher than expected, which decrease the shunt resistance 23. It has been reported that increasing the thickness or adding electron or hole blocking layers can effectively reduce the dark current 24–26. Thicker active layer could decrease conductance and dark current, but it also increases the response time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…But in practical condition, due to the disordered nature and unavoidable surface doping, the carrier density is always much higher than expected, which decrease the shunt resistance 23. It has been reported that increasing the thickness or adding electron or hole blocking layers can effectively reduce the dark current 24–26. Thicker active layer could decrease conductance and dark current, but it also increases the response time.…”
Section: Resultsmentioning
confidence: 99%
“…[23] It has been reported that increasing the thickness or adding electron or hole blocking layers can effectively reduce the dark current. [24][25][26] Thicker active layer could decrease conductance and dark current, but it also increases the response time. Blocking layers are usually a thin layer of donor at anode or acceptor at cathode, which have high bandgap and matched energy levels with electrodes that increases the barrier of reverse injection.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
See 1 more Smart Citation
“…At present, optoelectronic materials can be only processed by spin‐coasting or vapor deposition‐based traditional fabrication methods into the planar structures. [ 7,32–34 ] Facile and reliable stereo micro/nanofabrication method for multiple materials with designed function units and controlled morphologies is therefore of great significance. The self‐assembly of inorganic and organic nanomaterials in liquids directed by a space‐confined template has been demonstrated to yield micro/nanopatterns for applications in wearable sensors, integrated circuits, flexible displays, and waveguide devices.…”
Section: Figurementioning
confidence: 99%
“…[ 38 ] Many researches focus on the quality of the planar photosensitive film to improve the responsivity of the photodetector. [ 7,32,37 ] Owing to the strong ability of concentrating light into subwavelength volumes, the nanostructured photodetector realizes the detection of the property of incident light, such as the wavelength, polarization direction, incident angle, etc. [ 43 ] To compare the angular‐sensing responsivity, the absorption efficiency was regarded as the parameter to measure the difference.…”
Section: Figurementioning
confidence: 99%